Modeling and Performance Analysis of an Improved Movement-Based Location Management Scheme for Packet-Switched Mobile Communication Systems - Yun Won Chung; Jae Kyun Kwon; Suwon Park (The Scientific World Journal)
One of the key technologies to support mobility of mobile station (MS) in mobile communication systems is location management which consists of location update and paging. In this paper, an improved movement-based location management scheme with two movement thresholds is proposed, considering bursty data traffic characteristics of packet-switched (PS) services. The analytical modeling for location update and paging signaling loads of the proposed scheme is developed thoroughly and the performance of the proposed scheme is compared with that of the conventional scheme. We show that the proposed scheme outperforms the conventional scheme in terms of total signaling load with an appropriate selection of movement thresholds.